Perilaku Petani terhadap Budidaya Kakao di Subak-Abian Suci di Desa Gadungan, Kecamatan Selemadeg Timur, Kabupaten Tabanan (Jurnal Agribisnis dan Agrowisata, 2026)
Farmers' Behavior Regarding Cocoa Cultivation in Subak-Abian Suci in Gadungan Village, East Selemadeg District, Tabanan Regency. The purpose of this study was to determine the behavior that includes the knowledge, attitudes and skills of farmers towards cocoa cultivation in Subak-Abian Suci, Selemadeg Timur District, Tabanan Regency. This study uses qualitative data analysis techniques. This research was conducted in Subak-Abian Suci, Selemadeg Timur District, Tabanan Regency from July 2020 to December 2020. The collected data were analyzed using descriptive analysis methods. The results showed that the behavior of farmers in cacao cultivation in Subak-Abian Suci, East Selemadeg District, Tabanan Regency is in the good category. This behavior is supported by high knowledge in cocoa cultivation, good attitude, and skilled skills.
Keywords: behavior; knowledge; attitude; skill; farmer; cultivation; cacao